ANALISIS PENGARUH SANKSI PAJAK, TAX AMNESTY, DAN KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI: (Studi Kasus Pada Wajib Pajak Orang Pribadi yang Terdaftar di KPP Pratama Pasar Rebo) - Diah Maulia Sari Diah Maulia Sari; Ambar Ari Wibowo Ambar Ari Wibowo; Achmad Jaelani Achmad Jaelani (Cakrawala Akuntansi & Manajemen, 2023)
The purpose of this study was to determine how the effect of tax sanctions, tax amnesty, and quality of tax service services on individual taxpayer compliance at KPP Pratama Pasar Rebo. The data of this study were obtained from primary data through the distribution of questionnaires. The population in this study are individual taxpayers registered at KPP Pratama Pasar Rebo. By using multiple regression techniques, the results of this study indicate that Tax Sanctions have a significant positive effect on Individual Taxpayer Compliance, Tax Amnesty has a significant positive effect on Individual Taxpayer Compliance, and the Quality of Fiscus Service has a positive effect on Individual Taxpayer Compliance.